ANALISIS TINGKAT KESEHATAN PT. BPR WELERI MAKMUR DENGAN METODE CAMEL PADA PERIODE 2015-2018 - Nabila Saskia Noer Rizky; Winarni Winarni (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2020)
This study aims to assess and analyze the health level of PT. BPR Weleri Makmur if calculated using the CAMEL (Capital, Asset Quality, Management, Earning, and Liquidity) method in the 2015-2018 period based on Bank Indonesia Director's Decree No. 30/12 / KEP / DIR dated April 30, 1997. The component assessed is Capital (Capital) using CAR ratios, Asset Quality by using KAP ratios and PPAP ratios, Management using Management calculations using general management and risk management, earnings (earning) using the ROA ratio and the BOPO ratio, and Liquidity (Liquidity) using the Cash Ratio and LDR ratio.The results of the analysis and discussion showed that in the 2015-2018 period as a whole, the health level of PT. BPR Weleri Makmur is categorized in the healthy category, and the health level progress based on overall credit score at PT. BPR Weleri Makmur in the 2015-2016 period decreased.